Utilization of Video in Indonesian Language Learning in Elementary Schools in Indonesia - Anggraeni, Alviana Dwi; Setiawan, Andika Aji; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
Learning Technology was born from the reality of education and the audio-visual communication movement. Learning Technology was originally seen as equipment technology, which was related to the use of equipment, media and means to achieve educational goals or in other words teaching with audio-visual aids. One of the audiovisual- based teaching materials is video. Indonesian Language and Literature subjects are oriented towards the nature of learning Language and Literature which states that learning Indonesian is learning to use a good and correct language.This research is motivated by the problems that occur in learning Indonesian starting from the low level of concentration of students, then the difficulty of students in speaking in Indonesian, the difficulty of students in reading, and then the difficulty of students in writing. This study aims to determine the effect of using video media on learning outcomes in Indonesian language learning. The attention function of video media can attract attention and direct students' concentration on video material and the affective function of video media is able to arouse the emotions and attitudes of the audience. The results of using this video media in learning are to improve students' abilities in developing students' abilities in using Indonesian.